Designing the Websites of the Iraqi Electronic Newspapers and its Role in Attracting Visitors - عيادة ليث عبد الستار (ALBAHITH ALALAMI, 2016)
The researcher seeks to know the extent of applying the concept of design by Iraqi electronic press sites to provide media product with the acceptance of their browsers and ensure their repeated visits to such sites in the framework of the guiding rules for laser browsing. The researcher uses analytical study on a sample of six Iraqi electronic newspaper sites to identify the general features of their design and the methods of distribution of the structural elements of the pages. The researcher also conducts a field study on a sample of the surfers of electronic newspaper sites to see the extent of their evaluation to their design and the degree of their satisfaction.